Self-medication among non-healthcare students of the University of Sharjah, United Arab Emirates - Suleiman Ibrahim Sharif; Rubian Suleiman Sharif (Archives of Global Professionals, 2014)
Objectives: The objective of the following study is to estimate the prevalence of self-medication among university students and evaluate factors associated with the practice. Materials and Methods: This study was conducted during May, 2012 using a pre-validated questionnaire distributed to 250 students of the 4 years of study at the college of business administration. Data were analyzed using PASW Statistics for Windows, Version 18.0. Chicago: SPSS Inc and results are expressed as counts and percentages. Chi-square test was used to evaluate significant association among the study variables and P < 0.05 were considered to be statistically significant. Results: The response rate was 80% and all respondents were Arabs with 114 (57%) females and 86 (43%) males. Self-medication was practiced by 118 (59%) students and most (88.1%) of them obtained medications from pharmacies. About 21 (11%) respondents self-medicated with antibiotics. Only 34 (17%) and 16 (8%) of respondents were aware of bacterial resistance and rational drug use respectively. The most common reasons for self-medication were seeking quick relief (134, 67%), physician's advice of self-management (100, 50%), illness is minor (91, 45.5%). Common reasons against self-medication include risk of misdiagnosis of illness (160, 80%), risk of using the wrong medication (154, 77%), risk of adverse effects (140, 70%). Self-medication was practiced for headache or mild pain, eye and ear symptoms, gastric problems, cold, fever and allergy. Conclusion: Self-medication among non-healthcare students is common with high prevalence. Knowledge of students of reasons for and against self-medication was adequate, but awareness of respondents of rational drug use and risk of bacterial resistance in response to misuse was poor. Orientation courses/workshops directed to university students would be beneficial.